Analysis of Gobak Sodor Game in Physical Education - Subagio, Rohmad; Ruhiat, Yayat; Maryani, Nani (Dharmawangsa: International Journal of the Social Sciences, Education and Humanitis, 2025)
This simple research was conducted to analyze the values in the gobak sodor game in physical education. This type of research is library research, namely a study of theoretical and other research related to values, culture, and norms. The results of the study indicate that the values of the gobak sodor game can be applied in physical education.